PERANCANGAN SISTEM INFORMASI OPERASIONAL PENJUALAN TOKO SUNFLORIST - Victor; Darmansah (Computer Science and Industrial Engineering, 2024)
ABSTRACT Sun Florist is a business engaged in the sale of flowers. In managing its business operations, Sun Florist still faces challenges such as recording sales transactions, marketing and promoting products, and knowing sales turnover reports. In managing data such as product data, ordering data, and transactions, it is still done manually, recorded on paper. Additionally, document storage media such as purchase orders, invoices, and delivery orders are also recorded on paper and stored in folders, thus the encountered difficulties in tracing the data recording process flow due to lack of integration and requiring large storage space, and consumers needing relatively long time or having difficulty obtaining information about the required products. From these issues, this research produces a web-based operational sales information system to assist the company in business efficiency and effectiveness. The research methodology used includes interview, observation, and literature study, while the system development methodology utilizes the Rapid Application Development (RAD) method and the Unified Modeling Language (UML) as a system depiction tool, with PHP as the programming language and MySQL as the database.